Utilization of telerehabilitation in TKR patients: A systematic review. - Farnaz Salehian; Jahanpour Alipour; Somayyeh Zakerabasali (PLoS ONE)
Introduction Advanced telerehabilitation technology helps physiotherapists monitor the patient's treatment process after Total Knee Replacement. This study aimed to review the research on telerehabilitation after Total Knee Replacement, synthesize the findings related to their applications and features, and address evaluations made on them. Methods A systematic search was conducted in PubMed, Scopus, and Web of Science from 2019 through 2023. The authors selected the articles based on keywords and criteria and reviewed them in terms of title, abstract, and full text. Full-text articles and English language, focusing on telerehabilitation for TKR patients, preferably including mobile health applications and consistent with the research question, were considered for more review. Then, the MMAT (mixed methods appraisal) tool was used to assess each article. Finally, the selected articles were evaluated. The systematic review was registered through PROSPERO with registration ID: PROSPERO CRD42024533040. Result After reviewing databases, 183 articles were retrieved, then 84 duplicate articles were removed. Of the remaining 99 articles, 40 were deleted after reviewing the title and abstract because they were grey literature or irrelevant to TKR surgery, and 41 were deleted after reviewing the full text. Finally, 18 articles were included in this study and analyzed. The United States was the most common country that developed a telerehabilitation system. The most common use of this technology has been in education, treatment, and subsequent monitoring. Sensor and wearable activity trackers are the most common equipment used in studies. The most common study designs were randomized controlled trials (RCT) and observational studies, each of which accounted for 9 (50%) and 4 (22.22%), respectively. Conclusion Telerehabilitation can be as effective as traditional rehabilitation in improving the condition of patients after TKA. However, it is suggested that improvements should always be made to achieve better results of telerehabilitation. Most of the TKA apps in the reviewed studies showed significant effectiveness. Information and communication technology are used to provide high-quality, low-cost, continuous treatments. Soon, telerehabilitation will play a more prominent role and will be more popular.